2000
DOI: 10.1208/pt010435
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the pelletization process in a fluid-bed rotor granulator using experimental design

Abstract: This study examined the effect of rotor speed, amount of water sprayed, and atomizing air pressure on the geometric mean diameter and geometric standard deviation of pellets produced in a fluid-bed rotor granulator using a 23 factorial design and an optimization technique. Pellets were prepared by wet granulation. Equal amounts of microcrystalline cellulose, alpha-lactose monohydrate, and distilled water were used as the granulation liquid. The size and the size distribution of the pellets were determined by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 10 publications
(15 reference statements)
2
9
0
2
Order By: Relevance
“…Korakianiti et al demonstrated that the final product properties of the granules could be affected by the rotating speed used for fluid bed rotogranulation, although the precise nature of the properties would be dependent on the formulation and manufacturing methods used during the granulation process. 13) Taken together, the results of our current and previous studies of the GX system demonstrate that the final product properties could be affected by the rotating speed, although the extent of these effects would be dependent on the formulation and the manufacturing methods used during the granulation process. As shown in Table 4, the water content increased as the liquid binder flow rate (X 1 ) (p<0.001) increased or the atomization pressure (X 2 ) (p=0.006) or rotating speed (X 3 ) (p=0.002) decreased.…”
Section: )supporting
confidence: 61%
“…Korakianiti et al demonstrated that the final product properties of the granules could be affected by the rotating speed used for fluid bed rotogranulation, although the precise nature of the properties would be dependent on the formulation and manufacturing methods used during the granulation process. 13) Taken together, the results of our current and previous studies of the GX system demonstrate that the final product properties could be affected by the rotating speed, although the extent of these effects would be dependent on the formulation and the manufacturing methods used during the granulation process. As shown in Table 4, the water content increased as the liquid binder flow rate (X 1 ) (p<0.001) increased or the atomization pressure (X 2 ) (p=0.006) or rotating speed (X 3 ) (p=0.002) decreased.…”
Section: )supporting
confidence: 61%
“…Different types of screening designs, such as fractional factorial and Plackett-Burman screening designs, have been used for preformulation evaluations. [7][8][9][10] Response surface methodology (RSM) is used when only a few significant factors are involved in optimization. Different types of RSM designs include 3-level factorial design, central composite design (CCD), 11,12 BoxBehnken design, 13 and D-optimal design.…”
Section: Introductionmentioning
confidence: 99%
“…The type of coating technique strongly affects the film microstructure and thus affects the release mechanism and rate from pellets coated with polymer blends (Lecomte et al 2004). Pellets have increased in importance over the years due to their distinctive advantages in both technological and therapeutic aspects (Korakianiti et al 2000). When administered orally, therapeutic advantages include modification of drug release, division of dose strength, and free dispersion in the gastro intestinal tract (Abdul et al 2010).…”
Section: Introductionmentioning
confidence: 99%